2016
DOI: 10.1093/nar/gkw802
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA HOTAIR impacts on mesenchymal stem cellsviatriple helix formation

Abstract: There is a growing perception that long non-coding RNAs (lncRNAs) modulate cellular function. In this study, we analyzed the role of the lncRNA HOTAIR in mesenchymal stem cells (MSCs) with particular focus on senescence-associated changes in gene expression and DNA-methylation (DNAm). HOTAIR binding sites were enriched at genomic regions that become hypermethylated with increasing cell culture passage. Overexpression and knockdown of HOTAIR inhibited or stimulated adipogenic differentiation of MSCs, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 75 publications
7
132
0
Order By: Relevance
“…Separate studies on lncRNAs (such as Fendrr and Tug1) have indicated that they localize at various genomic regions by forming a RNA:DNA:DNA triplex. This conclusion was further validated by a matching result between genomewide triplexator's prediction of triplex helix DNA target sites by lncRNA HOTAIR and the peaks obtained using the CHIRP-seq experiment of HOTAIR (Kalwa et al 2016).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Separate studies on lncRNAs (such as Fendrr and Tug1) have indicated that they localize at various genomic regions by forming a RNA:DNA:DNA triplex. This conclusion was further validated by a matching result between genomewide triplexator's prediction of triplex helix DNA target sites by lncRNA HOTAIR and the peaks obtained using the CHIRP-seq experiment of HOTAIR (Kalwa et al 2016).…”
Section: Introductionmentioning
confidence: 61%
“…triplexator (Kalwa et al 2016). Our prediction of superlncRNAs binding sites is based on these preliminary studies that suggested that lncRNAs may bind to DNA via RNA: DNA:DNA triplex formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] A prominent example of an epigenetic-related long noncoding transcript is HOX transcript antisense RNA (HOTAIR) that exhibits an enormous regulatory potential in cells. 14 Nevertheless, although the role of HOTAIR in the establishment of histone methylation patterns has been well documented in numerous tumor entities, 11,13,[15][16][17][18][19] its possible involvement in the onset of aberrant DNA methylation is still poorly understood. It does so by serving as a molecular scaffold for Polycomb repressive complex 2 (PRC2) and the histone demethylase LSD1/CoR-EST/REST 13 and recruiting them to particular genomic loci likely via triple helix formation.…”
mentioning
confidence: 99%
“…It does so by serving as a molecular scaffold for Polycomb repressive complex 2 (PRC2) and the histone demethylase LSD1/CoR-EST/REST 13 and recruiting them to particular genomic loci likely via triple helix formation. 14 Nevertheless, although the role of HOTAIR in the establishment of histone methylation patterns has been well documented in numerous tumor entities, 11,13,[15][16][17][18][19] its possible involvement in the onset of aberrant DNA methylation is still poorly understood. Only few experimental studies have reported on the principle possibility of HOTAIRmediated aberrations of DNA methylation for several candidate genes in pathology.…”
mentioning
confidence: 99%